2010
DOI: 10.1577/m08-183.1
|View full text |Cite
|
Sign up to set email alerts
|

Smallmouth Bass Summer Habitat Use, Movement, and Survival in Response to Low Flow in the Illinois Bayou, Arkansas

Abstract: The southwestern edge of the natural range of smallmouth bass Micropterus dolomieu contains streams that become disconnected pools during summer primarily owing to hydrogeologic conditions, including high evapotranspiration rates. These conditions may complicate fisheries management by affecting fish behavior or mortality rates. The objectives of this study were to characterize summer habitat use by smallmouth bass, estimate the changes in the extent of available habitat, describe summer movement patterns, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…The longest movement we observed was 42.5 km, which was greater than the maximum 7.5 km movement of smallmouth bass previously documented in this stream (Todd & Rabeni ), and our maximum and average movement distances were greater than observed for most smallmouth bass populations, but within the range documented for smallmouth bass (Lyons & Kanehl ; Hafs et al. ). The longest documented migration by smallmouth bass was 109 km in a Wisconsin stream during autumn when water temperatures fell below 16 °C and in conjunction with a rain event (Langhurst & Schoenike ).…”
Section: Discussionsupporting
confidence: 48%
“…The longest movement we observed was 42.5 km, which was greater than the maximum 7.5 km movement of smallmouth bass previously documented in this stream (Todd & Rabeni ), and our maximum and average movement distances were greater than observed for most smallmouth bass populations, but within the range documented for smallmouth bass (Lyons & Kanehl ; Hafs et al. ). The longest documented migration by smallmouth bass was 109 km in a Wisconsin stream during autumn when water temperatures fell below 16 °C and in conjunction with a rain event (Langhurst & Schoenike ).…”
Section: Discussionsupporting
confidence: 48%
“…Accurate sampling of age-0 smallmouth bass is problematic because these fish are thought to use a variety of habitats (see Pert et al 2002 for a review), whereas adults are generally associated with deepwater habitats (Munther 1970;Probst et al 1984;Todd and Rabeni 1989;Brewer et al 2007;Dauwalter and Fisher 2008;Hafs et al 2010). Species that use a variety of habitat types in a stream are particularly difficult to sample accurately because commonly used sampling methods have biases related to habitat conditions, particularly depth, current velocity, and cover (Peterson and Paukert 2009).…”
mentioning
confidence: 99%
“…The physical factors related to the patterns observed in this study are unclear, though the physical and chemical consequences of urbanization have been well documented and include altered hydrology (Arnold et al 1982;Paul and Meyer 2001;Walsh et al 2005) and temperature (Paul and Meyer 2001). Extreme discharges during critical periods increase Smallmouth Bass mortality and reduce recruitment success (Peterson and Kwak 1999;Smith et al 2005;Hafs et al 2010) and high water temperatures restrict growth and reduce Smallmouth Bass densities (Sowa and Rabeni 1995;Zweifel et al 1999). The influence of pasture agriculture on aquatic fauna may be less pronounced than that found under well-studied, more intensive agriculture practices (e.g., row crop) (Meador and Goldstein 2003;Strayer et al 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Secondary production by several crayfish species (a primary food source of Smallmouth Bass: Rabeni 1992; Roell and Orth 1993;Roell and DiStefano 2010) was higher in nonpool channel units even though they represented only a small fraction of total stream area in Ozark streams (Brewer et al 2009). Additionally, Hafs et al (2010) indicated survival of Smallmouth Bass was lower than expected when moving-water channel units dried during summer. Collectively, these studies suggest channel units that are rarely, if ever, used by Smallmouth Bass are still very important to the overall fitness of this species.…”
Section: Discussionmentioning
confidence: 94%